Evaluation of HLA-B*57:01 and its effect on antiretroviral therapy in patients with human immunodeficiency virus infection: Experience of a University Hospital (Annals of Medical Research, 2021)
Aim: Before the decision to start abacavir (ABC), which is a member of the antiretroviral therapy (ART) combinations, the presence of the HLA-B*57:01 allele gene should be investigated in case of hypersensitivity to the drug. In recent years, many clinics tend to conduct “treat now” policy for HIV therapy. We aimed to evaluate HLA-B*57:01 test results and its effect on the initiation time of ART, combination and changing of ART.Materials and Methods: HLA-B*57:01 screening test was evaluated retrospectively in the HIV-infected patients admitted to Inonu University Faculty of Medicine Department of Infectious Diseases and Clinical Microbiology between January 2019 and December 2019.Moreover, the time frame of HLA-B*57:01 tests were evaluated along with the HIV confirmation test completion time. It was evaluated whether there was any effect on the start of treatment and treatment change.Results: Of the 47 HIV-positive patients 44 (93.6%) were male and 3 (6.4%) were female whose HLA-B*57:01 allele was screened. The mean age ± SD of these 47 patients was 37.7 ± 13.5 years. HLA-B*57:01 gene positivity was not detected in any of our cases. After HLA-B*57:01 test detection, ten (21%) of these patients were treated with ABC sulfate plus dolutegravir sodium plus lamivudine. Five of the patients were naive patients, while the other five patients were treatment experienced. HLA-B*57: 01 allele test completion time of the patients (mean ± SD) was 4.02 ± 2.35 days. HLA-B*57:01 completion time did not differ statistically in patients with and without treatment change (p=0.243). Conclusion: HIV infected individuals should be started to treat with ART soon after their diagnosis. To detect the HLA-B*57:01 allele in genomic DNA is important in this period. The fact that this procedure can be performed in centers following HIV-infected patients will positively affect the process of starting treatment.
Keywords: Effect on antiretroviral therapy; HIV; HLA-B*57:01; prevalance